The national association of realtors (John Wiley & Sons, 2007)
This one-of-a-kind resource gives you all the practical and insightful information you need to find your ideal home and get it at a great price. You’ll avoid common mistakes with step-by-step guidance on the buying process, as well as useful tools like checklists and guidelines and vital information on everything from financing to negotiations.